Penilaian Kualitas Akustik Masjid Raudhaturrahman Padang Tiji Menggunakan Simulasi Ecotect - Yani, Yulida (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
Mosque is a place of worship for Moslems. It has profound religious significance for the community; it is important that people feel serenity therein. In addition, they need to be able to hear sounds clearly so that they can perform their religious rituals like prayers smoothly and it is also crucial for them to hear speeches with a high degree of intelligibility. This study assessed the acoustic quality of Raudhaturrahman prayer's room, having a unique shape with the dome ceiling covering all dimensions of the building. This study aims at finding the condition, causes, and improving the acoustic quality to meet the prayer's room acoustic needs. This study specifically focused on calculating the background noise and reverberation time using the Ecotect Simulation method. The simulation result demonstrates that the calculation of reverberation time (RT) and the measurement of background noise have not met the desired standard. This study found that the value for RT with occupancy 0%, 50%, 100% is 18, 29s, 7, the 80s, and 4, 71s. In addition, the result of the background noise is 60 dB. In conclusion, the acoustic of the Raudhaturrahmah mosque prayer's room is of inferior quality since it does not meet the standard of reverberation time (RT) and background noise for the speech purpose of the room.